1999
DOI: 10.1002/(sici)1098-2744(199910)26:2<74::aid-mc2>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison of dibenzo[a,l]pyrene-DNA adduct formation by recombinant human cytochrome P450 microsomes

Abstract: Dibenzo[a,l]pyrene (DB[a,l]P), an extremely potent environmental carcinogen, is metabolically activated in mammalian cells and microsomes through the fjord-region dihydrodiol, trans-DB[a,l]P-11, 12-diol, to syn- and anti-DB[a,l]P-11,12-diol-13,14-epoxides (syn- and anti-DB[a,l]PDEs). The role of seven individual recombinant human cytochrome P450s (1A1, 1A2, 1B1, 2B6, 2C9, 2E1, and 3A4) in the metabolic activation of DB[a,l]P and formation of DNA adducts was examined by using (32)P postlabeling, thin-layer chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…On the other hand, mEH and CYP1B1 have been implicated in participating in the metabolic activation of DMBA 11, 21, 23. DB[ a,l ]P is metabolically converted to the ultimate form by CYP1A1, CYP1B1 and mEH 20, 24, 25. In the present study, in contrast to B[ a ]P and DMBA, DB[ a,l ]P induced a low level of CYP1A1 in the AhR−/− mouse skin.…”
Section: Discussionsupporting
confidence: 43%
“…On the other hand, mEH and CYP1B1 have been implicated in participating in the metabolic activation of DMBA 11, 21, 23. DB[ a,l ]P is metabolically converted to the ultimate form by CYP1A1, CYP1B1 and mEH 20, 24, 25. In the present study, in contrast to B[ a ]P and DMBA, DB[ a,l ]P induced a low level of CYP1A1 in the AhR−/− mouse skin.…”
Section: Discussionsupporting
confidence: 43%
“…In V79 Chinese hamster cells expressing either human P4501A1 or P4501B1, DB[a,l]P is oxidized to its fjord-region DEs (36). Studies with recombinant human P450 microsomes have further demonstrated that P450s 1A1 and 1B1 catalyze the activation of DB[a,l]P leading to formation of DNA adducts (37). Furthermore, a role for P4501B1 has also been supported by findings that Cyp1b1(-/-) mice have fewer tumors and a greater survival time as compared to WT mice treated intragastrically with DB[a,l]P (38).…”
Section: Discussionmentioning
confidence: 93%